New bioactive secondary metabolites from fungi: 2024 - Meiyan Bao; Ying Shi; Xiaoyi Gong; Yutong Guo; Jing Wang; Xiaofei Chen; Ling Liu (Mycology, 2025)
Fungi have been recognised as a prolific source of structurally unique secondary metabolites with promising pharmacological properties. This review comprehensively summarises the chemical architectures, bioactivities, and research strategies for new fungal-derived natural products, focusing on representative studies published in 2024. A total of 907 novel fungal-derived compounds are systematically cataloged (isomers are also contained in the total count), including 284 polyketides, 362 terpenoids, 28 steroids, 108 alkaloids, 75 peptides, and 50 glycosides, while highlighting cutting-edge methodologies such as metabolomics-guided discovery platforms and biosynthetic pathway engineering. By establishing connections between chemical novelty and therapeutic value, this review not only provides strategic guidance for fungal chemical diversity exploration but also illuminates their transformative potential in overcoming drug discovery bottlenecks.